APPLICATION OF MILLIMETER WAVE′S RADIOMETRIC SYSTEM FOR DETECTION OF MALIGNANT NEW GROWTHS OF MAMMARY GLANDS - V. V. Murav’iov; A. A. Tamelo; Y. L. Puturskiy; E. V. Shapoval; A. A. Leshik; D. I. Matveev; D. F. Molodkin; A. A. Popov (Приборы и методы измерений)
Developed and investigated radiometric system EHF (extremely high frequency) range for the diagnosis of tissue samples affected by carcinoma. EHF system are significantly higher than in the possibility of identifying a lower frequency range, as in UHF band (UHF band) and UHF (ultra high frequency) resolution of 1-3 mm are impossible. It was established that the affected carcinoma tissue samples are 3 dB lower transmittance compared to unaffected tissues. Analysis of the dependency of the harmonic components of the modulation signal passing through the examined tissue samples shows dramatic difference in the behavior of the harmonic components of the frequency domain. This phenomenon appears to altered tissue the presence of slumps that due to the interaction of electromagnetic waves with the tissue samples may be explained by the so-called stochastic resonance effect.